Planets to cosmology : essential science in the final years of the Hubble Space Telescope : proceedings of the Space Telescope Science Institute Symposium, held in Baltimore, Maryland, May 3-6, 2004 - Livio, Mario, 1945-; Casertano, Stefano (Cambridge University Press, 2006)
This 2006 book acknowledges the importance of identifying the most crucial science to be performed by the superb Hubble Telescope. With this goal in mind, the book presents a review of some of the most important open questions in astronomy. World experts examine topics ranging from extrasolar planets and star formation to supermassive black holes and the reionization of the universe. Special emphasis is placed on what astronomical observations should be carried out during the next few years to enable breakthroughs in our understanding of a complex and dynamic universe. In particular, the reviewers attempt to identify those topics to which the Hubble Space Telescope can uniquely contribute. The special emphasis on future research makes this book an essential resource for both professional researchers and graduate students in astronomy and astrophysics.
"Published for the Space Telescope Science Institute."
Keywords: Hubble Space Telescope (Spacecraft); Astronomy -- Research -- Congresses.; Space telescopes -- Research -- Congresses.; Astronomie -- Recherche -- Congrès.; Télescopes spatiaux -- Recherche -- Congrès.; SCIENCE -- Astronomy.; Astronomy -- Research; Planets; Hubble Space Telescope; Cosmology; Conference papers and proceedings